Effect of elastic contrast on the contribution of helical fibers into overall stiffness of a composites. (November 2017) - Trofimov, Anton; Abaimov, Sergey; Akhatov, Iskander; Sevostianov, Igor
Abstract: Compliance contribution tensors of helical inhomogeneities with various waviness parameters are calculated numerically using Finite Element Analysis (FEA) in dependence on the elastic contrasts between the fibers and matrix materials. The possibility to use replacement relation interconnecting compliance contribution tensors of the fibers having the same shape but different elastic constants is studied. It is shown that this relation in the form derived for ellipsoidal inhomogeneities leads to inappropriate error. We propose a modification of the replacement relation in order to increase accuracy of approximations. This modification provides satisfactory accuracy for fibers softer than the matrix.